A Salt‐Templated Strategy toward Hollow Iron Selenides‐Graphitic Carbon Composite Microspheres with Interconnected Multicavities as High‐Performance Anode Materials for Sodium‐Ion Batteries. Issue 2 (28th November 2018) - Choi, Jae Hun; Park, Seung‐Keun; Kang, Yun Chan
Abstract: In this work, a facile salt‐templated approach is developed for the preparation of hollow FeSe2 /graphitic carbon composite microspheres as sodium‐ion battery anodes; these are composed of interconnected multicavities and an enclosed surface in‐plane embedded with uniform hollow FeSe2 nanoparticles. As the precursor, Fe2 O3 /carbon microspheres containing NaCl nanocrystals are obtained using one‐pot ultrasonic spray pyrolysis in which inexpensive NaCl and dextrin are used as a porogen and carbon source, respectively, enabling mass production of the composites. During post‐treatment, Fe2 O3 nanoparticles in the composites transform into hollow FeSe2 nanospheres via the Kirkendall effect. These rational structures provide numerous conductive channels to facilitate ion/electron transport and enhance the capacitive contribution. Moreover, the synergistic effect between the hollow cavities within FeSe2 and the outstanding mechanical strength of the porous carbon matrix can effectively accommodate the large volume changes during cycling. Correspondingly, the composite microsphere exhibits high discharge capacity of 510 mA h g −1 after 200 cycles at 0.2 A g −1 with capacity retention of 88% when calculated from the second cycle. Even at a high current density of 5.0 A g −1, a high discharge capacity of 417 mA h g −1 can be achieved. Abstract : Hollow FeSe2 /graphitic carbon composite microspheres with interconnected multicavities are introduced as anodes for high‐performance sodium‐ion batteries. The synergistic effect between the hollow cavities within FeSe2 and the porous carbon matrix is responsible for superior performances of the composite microspheres for sodium‐ion batteries.